Meaning lyrics Slank As Media Communication Social Criticism - Adydhatya Della Pahlevi; Drs. Joyo Nur Suryanto Gono, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Music is used as a medium to convey the aspirations of social, political, and even become one of the media propaganda (information / opinions) to launch an ideological movement (idea / ideas). The lyrics is one of verbal communication media that have meaning in it. Research on the band Slank song